Anchorage capacity analysis using simulation - Huang, Shell Ying (2011)
With the substantial growth in marine traffic, anchorage space is now in high demand in certain hub ports. To provide decision support for port authorities, we have analyzed the usage of anchorages in recent years. The demands on the anchorages arise from the dynamically changing vessel mix and similarly complex service patterns. The utilization and the capacity of an anchorage space also depend heavily on the dispatching and allocation rules as well as the shape and areas of the anchorage. The complexity of the system studied is therefore beyond the current analytical tools, and hence simulation provides an effective means for the study. In this paper, we present a simulation-based capacity analysis on anchorages. The simulation model built is able to match the current scenarios well, and the analysis by simulation proves very useful in assessing anchorage utilization and capacity for future scenarios.